330 Investigating the clinical safety, efficacy, and immune modulation of combined XL888 and pembrolizumab in metastatic gastrointestinal malignancies. (10th December 2020) - Herting, Cameron; Zhang, Yuchen; Doxie, Deon; Farren, Matthew; Ware, Michael; Alese, Olatunji; Wu, Christina; Shaib, Walid; Akce, Mehmet; Zaidi, Mohammad; Ruggieri, Amanda; Dhodapkar, Madhav; et al.
Abstract : Background: Both pancreatic ductal adenocarcinoma (PDAC) and metastatic colorectal cancer (mCRC) have yet to widely benefit from T cell-targeted immunotherapy and have universally poor prognoses. Thus, enhancing the activity of immunotherapy is a high priority. Our laboratory recently reported that heat shock protein-90 (Hsp90) inhibition enhances the efficacy of PD-1 blockade in preclinical models of PDAC. 1 Mechanistically, Hsp90 inhibitors can limit activation of cancer associated fibroblasts (CAF) and promote infiltration of T cells when combined with PD-1 blockade. Based on these data, we are conducting a Phase Ib/II clinical trial to evaluate the combination of XL888 (Hsp90 inhibitor) and pembrolizumab in patients with metastatic pancreatic and colorectal cancers. We hypothesize that this combination will be safe and elicit pronounced microenvironmental changes, leading to enhanced efficacy. Methods: During the phase II portion, PDAC or mCRC patients (n=16 each) were randomized to receive a three week lead in with either pembrolizumab or pembrolizumab and XL888. Paired biopsies were obtained at baseline and at week two on treatment. A comprehensive panel of immunologic correlatives studies is being conducted to examine treatment-induced alterations in the tumor microenvironment and peripheral blood. Results: As of August 23rd, 2020, paired liver biopsy specimens from sites of metastasis have been successfully obtained from a total of 15 patients (n=7 PDAC and n=8 mCRC). These specimens underwent single cell mass cytometry (CyTOF) analysis to assess immunophenotypic markers of T and myeloid cells. Using this approach, we have generated a comprehensive view of the immune landscape at baseline and following treatment. These data will be validated by immunohistochemical analysis of FFPE biopsy specimens obtained in parallel at the time of CyTOF analysis. In addition to these correlative studies, using immortalized and primary CAF from PDAC patients, we have shown XL888 dampens production of IL-6 and other cytokines in vitro. The impact of XL888 on systemic cytokines and chemokines (n=48 total) in the peripheral blood from patients enrolled in the clinical trial is therefore also being assessed. Conclusions: Our correlative analysis of paired biopsies and peripheral blood from a novel clinical trial of XL888 and pembrolizumab will allow for further mechanistic insight into treatment-induced immune modulation. These data will also serve to validate whether alterations of CAF phenotype, cytokine and chemokine release, and T cell infiltration observed preclinically are mirrored in patients. Trial Registration: This clinical trial is underway and registered with the ID NCT03095781 . Ethics Approval: The study was approved by Emory University's Ethics Board, approval IRB00087397. Reference: Zhang Y, Ware MB, Zaidi M, Ruggieri AN, Olson B, Komar H, Farren MR, Nagaraju GP, Zhang C, Chen Z, Sarmiento J, Ahmed R, Maithel SK, El-Rayes BF, Lesinski GB. Heat shock protein-90 inhibition alters activation of pancreatic stellate cells and enhances the efficacy of PD-1 blockade in pancreatic cancer. Molecular Cancer Therapeutics 2020.